2017
DOI: 10.1111/trf.13984
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed xenon flash treatment inactivates bacteria in apheresis platelet concentrates while preserving in vitro quality and functionality

Abstract: The fXe treatment inactivated bacteria in apheresis PCs in plasma without additional chemical compounds. The fXe-treated PCs retained acceptable in vitro properties of PC quality and PLT functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…In our previous study, we found that fXe-treated PLTs showed sustained aggregation in contrast to untreated blood products PLTs collected by apheresis, which showed reversible aggregation in response to ADP (10 mM), and the sustained aggregability of fXe-PLTs was maintained during 6-day storage. 10 We initially found that the change of the aggregation pattern in Aph-PLTs from reversible to sustained depended on the fXe flash dose (Fig. 1).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In our previous study, we found that fXe-treated PLTs showed sustained aggregation in contrast to untreated blood products PLTs collected by apheresis, which showed reversible aggregation in response to ADP (10 mM), and the sustained aggregability of fXe-PLTs was maintained during 6-day storage. 10 We initially found that the change of the aggregation pattern in Aph-PLTs from reversible to sustained depended on the fXe flash dose (Fig. 1).…”
Section: Discussionmentioning
confidence: 95%
“…[7][8][9] Recently, we newly developed a method to prevent bacterial growth experimentally spiked into apheresis PCs using filtered-xenon (Xe) flash irradiation, named fXe treatment. 10 PCs in a UV-permeable bag were irradiated with UVC (wavelength of 200-290 nm) of Xe flash, filtered to exclude UVA, UVB, and visible light. Unlike INTERCEPT and Mirasol, fXe treatment requires no additional chemical compounds, but it is still in the experimental stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations